Pengaruh Kepemimpinan, Komunikasi, Motivasi Kerja, Dan Kedisiplinan Terhadap Kinerja Karyawan PT. Komatsu Remanufacturing Asia Plant Sudirman Di Departemen Produksi Balikpapan - Yusuf, H.Tamzil (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2014)
The purpose of this study was to determine whether the leadership, communication, motivation, and discipline employees simultaneously or partial effect on employee performance. Retrieve data through a questionnaire on 100 employees of PT. Komatsu Remanufacturing Asia Plant Production In Balikpapan. In addition, to determine which factors among the leadership, communication, motivation, and discipline is partially dominant influence on employee performance. Based on the analysis of data that have been presented can be concluded that the leadership, communication, job motivation and discipline employees work together has been linked to employee performance. The relationship between leadership, communication, motivation and discipline employees work together with the employee's performance as very good. This is shown by the coefficient of determination that leadership, communication, motivation and discipline employees work together to provide an effective contribution to improving employee performance up to 83.7%. Moreover, different test results showed that the variables of leadership, communication, self-motivation and discipline employees are also able to provide a partial influence on employee performance. From the results of different test is well known that the employee discipline factor contributed most to the increase in employee performance in PT. Komatsu Remanufacturing Asia Plant Production Department Sudirman In Balikpapan.Keywords: Leadership, Communication, Motivation, discipline, and employee performance